Organizacja ochrony środowiska w Polsce - Maciej Jabłoński (Studia Ecologiae et Bioethicae, 2013)
The organization of environmental protection in Poland is a result of both the country’s environmental policy, as well as programs connected with its function as part of the European Union. New challenges in the field of environmental protection are determining the way it is handled in Poland and in global policy.